Passively Q-switched 2.79-μm Er, Cr: YSGG laser based on pure water saturable absorber - Wang, Yinze; Huang, Lei; Kong, Haolin; Zhang, Yueyun; Cheng, Tingqing; Wang, Li; Jiang, Haihe (Frontiers in Physics, 2025)
Exploring suitable saturable absorber materials for the 2.79 μm waveband is always a focus in passive Q-switching laser technology. Pure water exhibits excellent fluidity, high chemical stability, and outstanding thermal properties; notably, its recovery capability suggests it could serve as an effective saturable absorber. This study validates the feasibility of saturable absorption with absorption darkening at 2.79 μm, analyzing the saturation absorption mechanism of water and the origin of absorption darkening. By designing a device to control the thickness of micron-scale water layers, controllable outputs of Q-switched single pulses and multipulses with microsecond intervals were achieved in a 2.79 μm Er, Cr: YSGG laser. With a water layer thickness of 7 μm and a repetition rate of 20 Hz, the maximum energy of the multi-pulse output reached 0.78 mJ, and the shortest single-pulse width was 286 ns. This provides a reference for the application of pure water as a saturable absorber and for the study of other hydroxyl-based saturable absorber materials.